Main content

## 8th grade (Eureka Math/EngageNY)

### Unit 4: Lesson 4

Topic D: Systems of linear equations and their solutions- Systems of equations: trolls, tolls (1 of 2)
- Systems of equations: trolls, tolls (2 of 2)
- Testing a solution to a system of equations
- Solutions of systems of equations
- Systems of equations with graphing
- Systems of equations with graphing
- Systems of equations with graphing: 5x+3y=7 & 3x-2y=8
- Systems of equations with graphing: y=7/5x-5 & y=3/5x-1
- Systems of equations with graphing: chores
- Systems of equations with graphing
- Systems of equations with elimination: 3t+4g=6 & -6t+g=6
- Systems of equations with elimination
- Systems of equations with elimination: x+2y=6 & 4x-2y=14
- Systems of equations with elimination: -3y+4x=11 & y+2x=13
- Systems of equations with elimination: 2x-y=14 & -6x+3y=-42
- Systems of equations with elimination: 4x-2y=5 & 2x-y=2.5
- Systems of equations with elimination: x-4y=-18 & -x+3y=11
- Systems of equations with elimination
- Systems of equations with elimination: 6x-6y=-24 & -5x-5y=-60
- Systems of equations with elimination challenge
- Systems of equations with substitution: 2y=x+7 & x=y-4
- Systems of equations with substitution
- Systems of equations with substitution: y=4x-17.5 & y+2x=6.5
- Systems of equations with substitution: -3x-4y=-2 & y=2x-5
- Systems of equations with substitution: 9x+3y=15 & y-x=5
- Systems of equations with substitution
- Systems of equations with substitution: y=-5x+8 & 10x+2y=-2
- Systems of equations with substitution: y=-1/4x+100 & y=-1/4x+120
- Systems of equations with elimination: apples and oranges
- Systems of equations with elimination: TV & DVD
- Systems of equations with elimination: King's cupcakes
- Systems of equations with elimination: Sum/difference of numbers
- Systems of equations with elimination: potato chips
- Systems of equations with elimination: coffee and croissants
- Systems of equations with substitution: coins
- Systems of equations with substitution: potato chips
- Systems of equations with substitution: shelves
- Systems of equations word problems
- Age word problem: Imran
- Age word problem: Ben & William
- Age word problem: Arman & Diya
- Age word problems
- Solutions to systems of equations: consistent vs. inconsistent
- Systems of equations number of solutions: fruit prices (1 of 2)
- Systems of equations number of solutions: fruit prices (2 of 2)
- Systems of equations number of solutions: y=3x+1 & 2y+4=6x
- Solutions to systems of equations: dependent vs. independent
- Number of solutions to a system of equations graphically
- Number of solutions to a system of equations graphically
- Forming systems of equations with different numbers of solutions
- Number of solutions to a system of equations algebraically
- Comparing Celsius and Fahrenheit temperature scales
- Converting Fahrenheit to Celsius

© 2023 Khan AcademyTerms of usePrivacy PolicyCookie Notice

# Systems of equations with substitution: y=4x-17.5 & y+2x=6.5

Learn to solve the system of equations y = 4x - 17.5 and y + 2x = 6.5 using substitution. Created by Sal Khan and Monterey Institute for Technology and Education.

## Want to join the conversation?

- Are you supposed to use the substitution method whenever you see the systems of equations?(5 votes)
- Systems of equations can be solved by graphing, elimination, or substitution. Which one you use comes down to the systems of equations you're solving for, and how much work you want to do. Some systems solve easier using elimination, while others solve quickly using substitution.(6 votes)

- What if the problem is

-5x + y= -2

-3 + 6y= -12

How would I figure out either the x value first or the y value first ?(4 votes)- You were already given the Y value, look:

-5x + y = -2 -3 + 6y = -12

y = -2 + 5x 6y = -9

y = -9/6

y = -3/2 <--- this is your Y value

Y = -9/3 (which is the same as -3/2), all you have to do to solve for X is substitute your Y value into the equation: -5x + 7 = -2

Here it goes:

-5x - 2/3 = -2

-5x = -2 +(2/3)

-5x = -4/3

x = (-4/3(4 votes)

- how would you solve this problem

x+y+7z=21

x+y+9z=29

x+y+4z=39(4 votes)- If you subtract the first one from the second one, you find that z = 4.

If you subtract the third one from the second one, you find that z = -2.

So, those equations don't have a solution.(2 votes)

- what if you have a problem like this:

-3x - 4y = 2

3x + 3y = -3

?(2 votes)- thanks so much! I needed help on this and now I have it!(3 votes)

- Solve by substitution.

System A and System B

3x-5y=13

2x+y=4(2 votes)- In the second equation, isolate y on the left by subtracting 2x from both sides. Now plug the new right hand side of equation two (i.e. 4 - 2x) for y in the top equation. The top equation is now in just one variable: x. Solve this for x. Plug this value for x into either equation and solve for y.

Please comment with your answer or any problems you run into.(2 votes)

- How do you solve by substitiution??

3x-2y=7

x+2y=5(2 votes) - I don't understand how to make one that looks like this:

-5x+3y=1

4x+y=23(1 vote) - what if you were to have -7x+8y=-5/ -2x+6y=6?(1 vote)
- -7x+8y=-5 AND -2x+6y=6 Solving by substitution:

Step 1: solve one of the equations for one of the variables. Pick either equation and either variable, just whichever is convenient.

-2x+6y=6

Divide both sides by -2 to get: x - 3y = - 3

Add 3y to both sides to get: x = 3y - 3

Use this to substitute for x into the other equation:

-7x+8y=-5

-7(3y - 3) + 8y = -5

-21y + 21 + 8y = -5

Add -21 to both sides to get: -21y + 8y = -26

Combine like terms to get: -13y = -26

Divide both sides by -13 to get: y = 2

Plug y= 2 into one of the equations and solve for x:

x = 3y - 3

x = 3(2) - 3

x = 3(4 votes)

- The problem is 840=(x+y) eq.1 & 840=(y-x)7 need to understand how to solve in substitution method HELP?(2 votes)
- how do i solve this

2x-3y=-24

x+6y=18(1 vote)- Try watching Sal's videos again before reading on.

Convert either of the equations into the form x = a*y + b or y = c*x + d

Substitute the value for x (or y) in the other equation

Solve this equation

Plug the result into either of the original equations

Solve that

Voila

So you could start by converting

x + 6y = 18

into

x = -6y + 18

Plug that into 2x - 3y = -24

2*(-6y + 18) - 3y = -24

Multiply into brackets

-12y + 36 - 3y = -24

Solve this equation for y

Plug the result into x = -6y + 18 to get x(2 votes)

## Video transcript

We have this system of
equations, y is equal to 4x minus 17.5, and y plus
2x is equal to 6.5. And we have to solve
for x and y. So we're looking for x's
and y's that satisfy both of these equations. Now, the easiest way to think
about it is we've already solved for y in this
top equation. Let me write it again. I'll write it in pink. We have y is equal
to 4x minus 17.5. So this first equation is
telling us, literally, by this constraint, y should be
4 times x minus 17.5. Now, the second equation says
whatever y is, we had 2 times x, and that should be 6.5. Well, the y here also has to
meet this constraint up here. It also has to meet the
constraint that it has to be 4 times x minus 17.5. So what we can do is, is we can
substitute this value for y into this equation. Let me be clear what
I'm doing. The second equation here is
y plus 2x is equal to 6.5. We know that y has to be equal
to this thing right here. y has to be equal to
4x minus 17.5. So let's take 4x minus 17.5,
and substitute y with that. So let's put that right there. So if we were to do that, if we
were to replace this y with 4x minus 17.5, because that's
what the first equation is telling us, then we get
4x minus 17.5, plus 2x is equal to 6.5. And now we have a single linear equation with one unknown. Let's solve for x. So first we have our x
terms. We have a 4x, and we have a 2x. We can group them or
add them together. 4x plus 2x is 6x. And then we have 6x minus
17.5 is equal to 6.5. Then we can get the 17.5 out
of the way by adding it to both sides of the equation. So this is negative 17.5, so
let's add positive 17.5 to both sides of this equation. And we are left with the
left-hand side is just going to be 6x, because these
guys cancel out. 6x is going to be equal to--
and 6.5-- see, 6 plus 17 is 23, and then 0.5
plus 0.5 is 1. So this is going to be 24. And then we can divide both
sides of this equation by 6. And you are left with x is equal
to 24 over 6, which is the same thing as 4. So we figured out the x value
for the x and y pair that satisfy both of these
equations. Now we need to figure
out the y value. And we can do that by taking
this x and putting it back into one of these equations. We can do it in to either one. We should get the
same y value. So let's just do this
top one up here. So if we assume x is equal to 4,
this top equation tells us y is equal to 4 times x, which
in this case is 4, minus 17.5. Well, this is equal to 16 minus
17.5, which is equal to negative 1.5. So y is equal to negative 1.5. So the solution to this system
is x is equal to 4, y is equal to negative 1.5. And you can even verify that
these two, they definitely work for the top one if you put
4 times 4, minus 17.5, you get negative 1.5. But they also work for
the second one. And let's do that. In the second one, if you take
negative 1.5, plus 2 times x-- plus 2 times 4-- what
does that equal? That's negative 1.5 plus 8. Well, negative 1.5
plus 8 is 6.5. So this x and y satisfy both
of these equations.